Correlation between Health Perception, Body Image, and Eating Habits in High School Students - Ichsan, Abdullah; Afriandi, Irvan; Gurnida, Dida Akhmad (Althea Medical Journal, 2016)
Background: Mental disorders, including eating disorders, mostly begin during youth. Moreover, negativeÂ body image is found to cause unhealthy eating habits in the context of several cross-cultural settings. ThisÂ study aimed to examine the correlation between health perception and body image with eating habitsamong high school students.Methods: A structured, anonymous questionnaire was distributed to students of a private high school inÂ Bandung, Indonesia in June-October 2014. The questionnaire included questions about health perception,Â body image, eating habits, body weight and height, and also other demographic parameters. The school wasÂ selected as the study object through purposive sampling, and 140 high school students (72 male and 68Â female) were ramdomly selected.Results: Male and female did not show considerable differences in health perceptions. Out of 13 statements,Â 12 statements of male respondents showed better body image than female. While in eating habits statements,Â female respondents seemed to maintain healthier eating habits than male respondents. No significantÂ correlation was observed between body image and eating habits (r=-0.015, p=0.858). There was significantÂ correlation between health perception and eating habits (r=0.374, p<0.001). Correlation between sex andeating habits was found (p=0.020), there was not significant relationship between eating habits and BodyÂ Mass Index (BMI) (p=0.368).Conclusions: The negative relationship between body image and eating habits is not significant. HoweverÂ there was a significant positive relationship between health perception and eating habits. Furthermore,Â there was correlation between sex and eating habits, while the positive relationship between eating habitsÂ and BMI was still not found. [AMJ.2016;3(2):216â21]DOI:Â 10.15850/amj.v3n2.770